PENDIDIKAN ANTI-BULLYING INKLUSIF: MEMBANGUN BUDAYA SEKOLAH RAMAH ANAK BERKEBUTUHAN KHUSUS DI SMP INKLUSI DI SURABAYA - Rafikayati, Ana; Isni Badiah, Lutfi; Nurrohman Jauhari, Muhammad; Nur Fisabilillah, Sabrina; Fuanindah, Lathifah (Kanigara, 2025)
Inclusive education is not enough to simply include children with special needs in regular classes, but must be supported by a school culture that welcomes diversity, creates a sense of belonging, and promotes healthy social relations. This culture does not just grow, but must be built consciously and systematically through inclusive education programs, including anti-bullying education. Teachers of Children with Special Needs need to be equipped with insight into Anti-Bullying ABK so they can implement it in their respective schools. Considering this, the Workshop on Anti-Bullying ABK is very important to be implemented. The results of this activity were an increase in the understanding teachers about the importance of the anti-bullying movement and skills in compiling anti-bullying teaching modules